International comparison of health spending and utilization among people with complex multimorbidity. (5th August 2021) - Figueroa, Jose F.; Papanicolas, Irene; Riley, Kristen; Abiona, Olukorede; Arvin, Mina; Atsma, Femke; Bernal‐Delgado, Enrique; Bowden, Nicholas; Blankart, Carl Rudolf; Deeny, Sarah; Estupiñán‐Romero, Francisco; Gauld, Robin; et al.
Abstract: Objective: The objective of this study was to explore cross‐country differences in spending and utilization across different domains of care for a multimorbid persona with heart failure and diabetes. Data Sources: We used individual‐level administrative claims or registry data from inpatient and outpatient health care sectors compiled by the International Collaborative on Costs, Outcomes, and Needs in Care (ICCONIC) across 11 countries: Australia, Canada, England, France, Germany, the Netherlands, New Zealand, Spain, Sweden, Switzerland, and the United States (US). Data Collection/Extraction Methods: Data collected by ICCONIC partners. Study Design: We retrospectively analyzed age–sex standardized utilization and spending of an older person (65–90 years) hospitalized with a heart failure exacerbation and a secondary diagnosis of diabetes across five domains of care: hospital care, primary care, outpatient specialty care, post–acute rehabilitative care, and outpatient drugs. Principal Findings: Sample sizes ranged from n  = 1270 in Spain to n  = 21, 803 in the United States. Mean age (standard deviation [SD]) ranged from 76.2 (5.6) in the Netherlands to 80.3 (6.8) in Sweden. We observed substantial variation in spending and utilization across care settings. On average, England spent $10, 956 per person in hospital care while the United States spent $30, 877. The United States had a shorter length of stay over the year (18.9 days) compared to France (32.9) and Germany (33.4). The United States spent more days in facility‐based rehabilitative care than other countries. Australia spent $421 per person in primary care, while Spain (Aragon) spent $1557. The United States and Canada had proportionately more visits to specialist providers than primary care providers. Across almost all sectors, the United States spent more than other countries, suggesting higher prices per unit. Conclusion: Across 11 countries, there is substantial variation in health care spending and utilization for a complex multimorbid persona with heart failure and diabetes. Drivers of spending vary across countries, with the United States being the most expensive country due to high prices and higher use of facility‐based rehabilitative care.